PERANCANGAN PROGRAM APLIKASI PENGENDALIAN KUALITAS PRODUK PADA CAFE BATAVIA JAKARTA - Olga Hanny Olivia (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Cafe Batavia is a company engaged in the sale of food and beverages. Problems encountered in this company is not terkintrolnya where the quality of goods or raw materials elah received. Coupled with the booking system and calculation of stock uncontrolled and still manual. Cafe Batava is still collecting data manually. Quality control is needed in this case to provide more thorough information about any goods that pass quality check and does not pass a quality check.One way that companies can improve product quality is to implement a quality control method is quite popular in use ie six sigma with the basic concept of a continuous effort to prevent any defective goods with a large quantity.